Pharmacological inhibition of mtorc2 reduces migration and metastasis in melanoma - Guenzle, Jessica; Akasaka, Harue; Joechle, Katharina; Reichardt, Wilfried; Venkatasamy, Aina; Hoeppner, Jens; Hellerbrand, Claus; Fichtner-Feigl, Stefan; Lang, Sven A. (International Journal of Molecular Sciences, 2021)
Despite recent advances in therapy, liver metastasis from melanoma is still associated with poor prognosis. Although targeting the mTOR signaling pathway exerts potent anti-tumor activity, little is known about specific mTORC2 inhibition regarding liver metastasis. Using the novel mTORC2 specific inhibitor JR-AB2-011, we show significantly reduced migration and invasion capacity by-impaired activation of MMP2 in melanoma cells. In addition, blockade of mTORC2 induces cell death by non-apoptotic pathways and reduces tumor cell proliferation rate dose-dependently. Furthermore, therapy with JR-AB2-011 as determined by in vivo imaging and necropsy. Hence, our study for a significant reduction of liver metastasis was detected in a syngeneic murine metastasis model upon the first time highlights the impact of the pharmacological blockade of mTORC2 as a potent novel anti-cancer approach for liver metastasis from melanoma.
CRIS-Team Scopus Importer:2021-01-08
Keywords: Melanoma; Metastasis; Migration; MTORC2